Do peer firms impact corporate investment policies? - Muhammad Mudassar Anwar; Muhammad Ramazan Akhtar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
Peer effect is attractive as firms try to mimic financial decisions taken by one another. The current study explores the impact of peers' investment decisions on corporate firm's investment decisions. To capture this essence, the study utilized firm-specific characteristics as well as peer firm-specific characteristics mainly growth, leverage, market to book ratio, free cash flow and stock return. In this study, the corporate accounting data relating to firms' investment policies is taken from the published annual audited reports of the firms for the period between 2005 and 2015. GMM fixed effect model is used for data analysis. The results of the study reveal significant impact of peers' investment policies on corporate firm's investment decisions.
Keywords: 330; peer effect; mimicking behavior; investment policy; leverage; cash flow